Pronominal address among Russian Germans in the Altair Krai – preliminary results of empirical data - Tauschwitz, Yves-Oliver (Linguistik Online, 2014)
The German personal pronoun Ihr is the origin of an interesting difference in the address system of Russian Germans and Germans. Whilst the usage of this pronoun has shifted strongly in the last 100 years in Germany, it has been revealed that Russian Germans still use it in the same way as their predecessors. But since these observations date back more than ten years, the purpose of this study was to explore the current usage of personal pronouns among Russian Germans in the Altai Krai. For that purpose fourteen Russian Germans from the German National District and Barnaul were interviewed. This study combines quantitative and qualitative methods, as each respondent was presented a survey and went through a guided interview. As a result, two decision trees for the interviewed Mennonites on the one hand, and Catholics and Lutherans on the other hand, could be composed. The interviewed Russian Germans obviously still adhere to power semantics in the family, among friends and at work. While the Catholics and Lutherans were still employing Ihr, Mennonites used See in order to formally address one interlocutor. This study has also been able to identify Russian Germans' usage of the German dialect in the family and with friends.